2014
DOI: 10.1128/jb.02282-14
|View full text |Cite
|
Sign up to set email alerts
|

Proline Metabolism IncreaseskatGExpression and Oxidative Stress Resistance in Escherichia coli

Abstract: The oxidation of L-proline to glutamate in Gram-negative bacteria is catalyzed by the proline utilization A (PutA) flavoenzyme, which contains proline dehydrogenase (PRODH) and ⌬ 1 -pyrroline-5-carboxylate (P5C) dehydrogenase domains in a single polypeptide. Previous studies have suggested that aside from providing energy, proline metabolism influences oxidative stress resistance in different organisms. To explore this potential role and the mechanism, we characterized the oxidative stress resistance of wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 65 publications
1
71
0
Order By: Relevance
“…abortus DputR is hypersensitive to oxidative stress in vitro It has been shown previously that bacterial Put systems are linked to oxidative stress [28][29][30]. To test the hypothesis that putR and putA in B. abortus are required for the ability of the bacteria to cope with oxidative stress, we cultivated the bacteria in liquid medium, and then the cultures were treated with hydrogen peroxide (H 2 O 2 ) at a final concentration of 10 mM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…abortus DputR is hypersensitive to oxidative stress in vitro It has been shown previously that bacterial Put systems are linked to oxidative stress [28][29][30]. To test the hypothesis that putR and putA in B. abortus are required for the ability of the bacteria to cope with oxidative stress, we cultivated the bacteria in liquid medium, and then the cultures were treated with hydrogen peroxide (H 2 O 2 ) at a final concentration of 10 mM.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the PutA acts to induce anti-oxidative stress genes in E. coli through production of reactive oxygen species (ROS) [28,30]. The exact mechanism for this ROS production was not explored, but it was suggested that ROS were generated through the increased flux through the electron transport chain, leading to the formation of superoxide species and production of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the physiological state of S. Aureus , B. subtilis and E. coli , cells in Luria Lertani (LB) broth varies greatly with time . The addition of Pro‐Pro increased the growth of these bacteria, thus revealing that this peptide is also stimulating the growth of bacteria, perhaps by acting as a proteogenic molecule for them ,. However in the presence of the Au(III)‐conjugated Pro‐Pro, the growth was altered and decreased (ESI).…”
Section: Figurementioning
confidence: 99%
“…Proline biosynthesis has been linked to resistance to oxidative stress through the proline catabolic pathways involving the bifunctional flavoenzyme, PutA, which is both a proline dehydrogenase (generates P5C) and Δ 1 ‐pyrroline‐5‐carboxylate (P5C) dehydrogenase (generates glutamate). Furthermore, proline catabolism involving PutA was found to be involved in the generation of hydrogen peroxide (Zhang et al ., ). These observations suggest it is not a defect in the biosynthesis of proline per se , but rather the accumulation of the intermediate metabolite, P5C, which is responsible for the intracellular growth defects.…”
Section: Metabolites Available To S Typhimurium Within Host Cellsmentioning
confidence: 99%